How Do We Help Nurses Deal with Their Grief? - A perspective - Betriana, Feni (REAL in Nursing Journal, 2019)
Dying and death of patients are continuous events in healthcare setting. Even in the high technological situation, those are unavoidable and become parts of nurses` everyday work, especially in some units such as emergency department (ED), intensive care unit (ICU), high care unit (HCU), etc. Facing dying and death of patients were reported to cause nurses` grief (Shorter & Stayt, 2009). In some cases, the grief may stay longer than it should be.